Clinicoepidemiological Profile of Short Stature at a Tertiary Care Centre in North India - Rajan, Mahima; Vaswani, Narain Das; Lekhwani, Seema; Bansal, Mohit (Indian Journal of Child Health, 2020)
Background: Short stature (SS) is a common pediatric problem. The goal of the evaluation of a child with SS is to identify the subset of children with pathologic causes so that appropriate timely intervention can be made. Aim: The aim of the study was to study the clinical, epidemiological, and etiological profile of SS at a tertiary hospital of north India. Materials and Methods: This was an observational analytical study and was conducted in the department of pediatrics, over a period of 1 year (October 2016– September 2017). A total of 100 children aged 3–14 years, with height <?2SD below the mean height for age and sex, were studied. Clinical history, examination, and laboratory evaluations were done to assess the cause of SS and the data were analyzed using appropriate statistical methods. Results: About 55% were female and 45% were male. The causes of SS were found to be familial SS (28%), celiac disease (17%), chronic diseases (15%), constitutional growth delay (12%), hypothyroidism (11%), small for gestational age babies with no catch-up growth (10%), use of corticosteroids (4%), and growth hormone deficiency (3%). Conclusion: Chronic systemic illnesses and malnutrition still form a major chunk in the etiological profile of SS in India. Celiac disease should be considered with a high index of suspicion as one of the etiologies of SS.